Kompilasi Penentuan Sesar berdasarkan Data Struktur Geologi Permukaan dan Implikasinya terhadap Keberadaan Sesar Mataram di Daerah Bokoharjo, Prambanan, Sleman, Yogyakarta - Kurniawan, Sandi; Rizqi, Al Hussein Flowers; Erlandi, Muhammad; Nadhip, Muhammad; Alansyah, Apriko Yudhan; Wibisono, Dharmawan Catur; Winarti, Winarti; Fatih Qodri, Muhammad (ReTII, 2023)
The devastating Yogyakarta earthquake of 2006 had its epicenter on the Opak Fault. Several earthquake incidents also occurred in 2016 and were centered in the middle of urban Yogyakarta. The cause of the earthquake is still interpreted as a fault movement, which is suspected to have a different direction from the Opak Fault. Research on the Fault in a different direction from the Opak Fault is still minimal and needs to be studied. The research area covers the area around the Boko Hills, to be precise, in Bokoharjo, Prambanan, Sleman, Yogyakarta. This study intends to examine surface geological structure data, which allegedly shows a west-east direction of fault movement. The purpose of this study is to identify a west-east trending fault and its relationship to the existence of the Mataram Fault. The research method used is semi-detailed mapping and tracing of geological structure data in the form of joints (shear fracture and gash fracture). Surface data indicating the presence of faults is indicated by a step fault. The results of the study show that the main fault moves in a west-east direction with a stereonet projection throughsoftware Dips have directions N 270OE/ 54O. The direction of the stress force has a north-south direction around N 313 E/ 78O. This west-east trending fault is related to the existence of the Mataram Fault which has a west-east direction and cuts the Opak Fault in the Bokoharjo area. The intersection of the Mataram Fault and the Opak Fault results in a deflection of the Opak River and the appearance of a spring (Umbul Sidomulyo) around the Opak River bend. Keywords : Structural geology, Mataram fault, earthquake, Bokoharjo, Yogyakarta